Reformulation: the Impact of the Sun's Spatial Size and Orbital Path on the Calculation of Zuhr Prayer Start Time - Rochman, Arman Abdul; Utama, Judhistira Aria (Al-Marshad: Jurnal Astronomi Islam dan Ilmu-Ilmu Berkaitan, 2024)
The determination of the start time for Zuhr prayer in its calculation does not refer to the actual natural phenomena but is based on the Sun's transit at the meridian, plus a specific margin of safety (ihtiyath) that differs from the ihtiyath values used for other prayer times. This study demonstrates the duration of the Sun's decline throughout the year to validate the use of this specific ihtiyath for Zuhr. The calculation of the Sun's decline duration uses data on solar declination and semi-diameter, which are then simulated for the entire year of 2025. The simulation results show that the duration of the Sun's decline ranges from 63.64 to 70.85 seconds. When rounding up the duration of the decline and adding an ihtiyath value of 2 minutes (similar to the ihtiyath for other prayer times), the conclusion from this study suggests that the ihtiyath for Zuhr should be 4 minutes. However, it would be better if the calculation of the start time for Zuhr prayer used corrections based on solar declination and semi-diameter data to indicate the actual phenomenon of the start time for Zuhr prayer and to avoid misconceptions by using a uniform ihtiyath for all prayer times.